2016
DOI: 10.4149/km_2016_3_257
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of titanium carbide particulate reinforced AA6061 aluminum alloy composites using stir casting

Abstract: Stir casting is an economical method to produce aluminum matrix composites. In the present work, composites of aluminum alloy AA6061 reinforced with various amounts (0, 5, 10 and 15 wt.%) of TiC particles were prepared by stir casting technique. X-ray diffraction patterns of the prepared composites clearly revealed the incorporation of TiC particles without the presence of any other compounds. The microstructures of the composites were studied using optical and scanning electron microscopy. It was observed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The potency of the composite is impacted by the nature of the reinforcement particles phase. The findings of the present investigations are consistent with those of earlier researchers [28].…”
Section: Xrd Characterizationsupporting
confidence: 94%
See 1 more Smart Citation
“…The potency of the composite is impacted by the nature of the reinforcement particles phase. The findings of the present investigations are consistent with those of earlier researchers [28].…”
Section: Xrd Characterizationsupporting
confidence: 94%
“…Also, the reinforcement particles protect the softer matrix. The hard reinforced particles thus restrict deformation and resist indentation when touched [28]. The increased hardness may also be because SiC and BLA withstand the major load transferred by the matrix.…”
Section: Hardness Measurementmentioning
confidence: 99%
“…Soorya Prakash et al [ 54 ] stated that the inclusion of rock dust particles to the AA6061 alloy enriched the wear protection of the AAMCs. Moses et al [ 55 ] observed that the wear resistance of the AAMCs was enhanced with an increase in the weight percentage of TiCp. Also, the hard TiC contents include the plain matrix, which helps to decrease the PD affected by the improved wear resistance of the composite.…”
Section: Resultsmentioning
confidence: 99%
“…Another factor for the increase in hardness of the composite samples is because of the bonding strength between the matrix and the reinforcement. The wetting characteristic between the ZnO and AA6061 matrix was perfect and so it does not form the brittle reaction layers (Moses et al , 2016). Hence, the hardness of the fabricated composite samples is high.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various fabrication processes, stir casting was widely considered to fabricate AMCs because of its flexibility in processing and material handling, and its high economic advantages (Surappa, 2003). AA6061 has excellent mechanical properties such as high strength and ductility, including high corrosion resistance (Pazhouhanfar and Eghbali, 2018; Moses et al , 2016) and it is highly flexible for manufacturers to modify based on the requirements. Fabricating the aluminium alloys reinforced with hard ceramic particles makes changes in morphology by novel grain refinements and it leads to accomplishment of good mechanical properties (Sudarshan and Surappa, 2008).…”
Section: Introductionmentioning
confidence: 99%